2010
DOI: 10.1038/embor.2010.161
|View full text |Cite
|
Sign up to set email alerts
|

One man's meat is another man's poison

Abstract: Why does one person like cucumber while another hates it? Understanding the causes of our innate and idiosyncratic food preferences has real implications for encouraging children and adults to eat a healthy diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
3
0
2
Order By: Relevance
“…It is an important finding of the current study that children appear to be influenced by their mothers intake at such an early age, as it supports the literature on social learning that mothers can act as role models for their children by consuming a wide variety of nutritious foods, including fruit and vegetables, in order to increase the likelihood that their children will accept the same (Wardle & Cooke ). This highlights opportunities for randomised controlled trials directed at improving mothers' diet quality in order to positively impact child diet quality.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is an important finding of the current study that children appear to be influenced by their mothers intake at such an early age, as it supports the literature on social learning that mothers can act as role models for their children by consuming a wide variety of nutritious foods, including fruit and vegetables, in order to increase the likelihood that their children will accept the same (Wardle & Cooke ). This highlights opportunities for randomised controlled trials directed at improving mothers' diet quality in order to positively impact child diet quality.…”
Section: Discussionsupporting
confidence: 81%
“…Wardle & Cooke () argue that an individual's experience with food can override this innate or genetic predisposition. Animal and human studies suggest that food preferences can be socially transmitted through food behaviours modelled in the home or by peers, and that feeding behaviours such as rewards and positive attention for healthy eating tend to increase acceptance (Wardle & Cooke ). Repeated exposure through ingestion of unfamiliar foods also leads to increased acceptance of that food (Cooke ).…”
Section: Discussionmentioning
confidence: 99%
“…The preference for sweet taste seems to be innate in humans. Almost all newborns positively react to sugar solutions as opposed to lemon juice solutions, according to their facial expressions [ 32 ]. In a study conducted with children (9–10 years old), adolescents (14–16 years old), and adults (20–25 years old) that investigated the perception of intensity of the sweet taste in solutions containing different sugar levels, the authors observed that children had a higher preference for high concentrations of sugar than teenagers, who had a higher preference than adults.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos também apontam que indivíduos tasters não têm preferência por alimentos como chá verde, café e bebidas alcoólicas (61,(115)(116)(117) . (120) .…”
Section: Tas1r2 Sabor Doce E Consumo Alimentarunclassified
“…É reconhecido que evitar novas substâncias reduz a possibilidade de envenenamento a partir de plantas ou animais tóxicos. Curiosamente, a neofobia é mínima durante a primeira infância, quando a ingestão alimentar da criança é em grande parte ditada por adultos, mas aumenta rapidamente à medida que a independência da criança cresce (120,126) . Humanos e animais são mais propensos a aceitar um alimento desconhecido quando observam seu consumo, sem consequências deletérias, por outros membros de sua espécie ou família (126,128,129) .…”
Section: Figura 12unclassified